2014
DOI: 10.1111/ajpy.12034
|View full text |Cite
|
Sign up to set email alerts
|

Social networking site use: Linked to adolescents' social self‐concept, self‐esteem, and depressed mood

Abstract: Adolescents spend a substantial amount of time using social networking sites (SNSs); however, little is known regarding whether such use is associated with indicators of adjustment. The present study employed a multidimensional measure of SNS use to investigate the link between Australian adolescent SNS use and indicators of adjustment. Youth (N = 1,819, 55% female) from 34 diverse high schools across Western Australia were surveyed. The results showed that frequency of SNS use was linked to higher social self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
92
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 173 publications
(104 citation statements)
references
References 22 publications
7
92
0
5
Order By: Relevance
“…This scale was based on the mean for three items used in previous research where the validity of the scale has been ascertained (Blomfield Neira & Barber, ). Items were measured on a 6‐point scale from 1 ( never ) to 6 ( daily ) and include: “How often do you feel satisfied with who you are?” The items were reverse coded with higher scores representing low self‐esteem.…”
Section: Methodsmentioning
confidence: 99%
“…This scale was based on the mean for three items used in previous research where the validity of the scale has been ascertained (Blomfield Neira & Barber, ). Items were measured on a 6‐point scale from 1 ( never ) to 6 ( daily ) and include: “How often do you feel satisfied with who you are?” The items were reverse coded with higher scores representing low self‐esteem.…”
Section: Methodsmentioning
confidence: 99%
“…By analyzing the images that five young people aged 22-25, posted on Instagram, Marcus (2015) concluded that Instagram exists to enable personal self-promotion. Indeed, "selfies"-photographs that individuals take of themselves [37], typically with webcams or smartphones-are among the most popular types of posts. Marcus (2015) insisted that unlike Facebook, Instagram is based more on one's personal identity than one's relational identity [35].…”
Section: Instagrammentioning
confidence: 99%
“…Facebook provides not only a forum for communication via instant messaging but also allows youth to share personal content (e.g., photographs, videos, status updates, and profile posts), and to provide and receive feedback (e.g., commenting on others' shared content and reacting to content by clicking on emotions such as, "like," "love," "wow," "angry," or "sad") (Neira, Corey, & Barber, 2014;Shaw, Timpano, Tran, & Joormann, 2015). Additionally, Facebook allows for passive use by navigating through the site without posting or reacting to content.…”
Section: Introductionmentioning
confidence: 99%
“…Privacy settings allow users to routinely adjust who has access to, and who is blocked from viewing their shared content (Shaw et al, 2015). Through Facebook, adolescents can observe others anonymously, control their self-image, and make social comparisons with others (Ellison, 2007;Neira et al, 2014;Shaw et al, 2015). The rising use of SNSs has received considerable attention worldwide and reviews on their impact on users' mental health are mixed Sampasa-Kanyinga & Lewis, 2015;Valkenburg, Koutamanis, & Vossen, 2017;Verduyn, Ybarra, Résibois, Jonides, & Kross, 2017).…”
Section: Introductionmentioning
confidence: 99%